If it's not what You are looking for type in the equation solver your own equation and let us solve it.
49=7(x-1)(x-1)
We move all terms to the left:
49-(7(x-1)(x-1))=0
We multiply parentheses ..
-(7(+x^2-1x-1x+1))+49=0
We calculate terms in parentheses: -(7(+x^2-1x-1x+1)), so:We get rid of parentheses
7(+x^2-1x-1x+1)
We multiply parentheses
7x^2-7x-7x+7
We add all the numbers together, and all the variables
7x^2-14x+7
Back to the equation:
-(7x^2-14x+7)
-7x^2+14x-7+49=0
We add all the numbers together, and all the variables
-7x^2+14x+42=0
a = -7; b = 14; c = +42;
Δ = b2-4ac
Δ = 142-4·(-7)·42
Δ = 1372
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{1372}=\sqrt{196*7}=\sqrt{196}*\sqrt{7}=14\sqrt{7}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(14)-14\sqrt{7}}{2*-7}=\frac{-14-14\sqrt{7}}{-14} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(14)+14\sqrt{7}}{2*-7}=\frac{-14+14\sqrt{7}}{-14} $
| 5-10y=6y-37 | | 4a-8=+a | | 4=3r- | | 60x-10+50=108x-8 | | 20-x=35-x2 | | 27=3n-12n | | .3(p+7)-(4p-1)=-5(2p-3)+1 | | 8x+18=288 | | 2x-2=4+8 | | 1/4+2=x | | -7x=-7.7 | | d/12+25=28 | | 4k-6=2k+8 | | -7=-15a+12 | | 23y2–26y=0 | | 8r-7r=4 | | 24x-10=20x-17 | | 4g+3=23-g | | 4x+5=17* | | 5(y+2)=50+y | | 6a=a=14 | | 6p=1.5 | | -2r-1=-15 | | 10x-3(x+2)+6=1 | | 3(k+–3)=–6 | | h−3+7=8 | | 6x+4+35=75 | | 13.9y=36.8 | | 21x+17=30x-19 | | 274=53-y | | –6h+20=3−6h+17 | | 0=X^3-3x^2+4x-4 |